PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS VI SDN 012 PEKAN ARBA - Arpandisyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the lack of mathematics learning outcomes Class VI SDN 012 Pekan Arba, this is evidenced by the acquisition of the average value obtained at 65, other than that of the 20 students were only 8 students (40.00%), which reached KKM. Based on this the researchers conducted a study to implement cooperative learning model think pair squer (TPS). This study is a class action, which was carried out as much as two cycles consisting of two meetings. Based on the research data showed that students' mathematics learning outcomes in each cycle has increased, on the basis of the number of students who score reached KKM is 10 students (50.00%), the first UH KKM number of students who achieve an increase in the number of students is 75, 00%, and at UH II, the number of students who reached KKM increased by 85.00%. Therefore, it can be concluded that the implementation of cooperative learning model think pair squer (TPS) can improve learning outcomes sixth grade mathematics students SDN 012 Pekan Arba.